Compliment and compliment response strategies from photo comment sections as used by Filipino Facebook users - Mejorada, Kimberly M. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2022)
Compliments and compliment responses are prevalent in Social Networking Sites (SNS), like Facebook. This study was conducted to investigate the compliment and compliment response strategies produced by Facebook users in photo comment sections. This study used the qualitative and quantitative design in spotting and analyzing the felicity conditions of compliment and compliment response strategies produced by thirty participants. Using Zhang’s (2013) taxonomy for compliment strategies, the results showed that the most used approach in complimenting is Explicit compliment, in which the complimenters used adjectives that carry positive values. Meanwhile, using Yu’s (2004, cited in Tamimi Sa’d’, 2015) taxonomy for categorizing compliment response strategies, the Face Relationship-related Response Strategy is the most common strategy used by the complimentees in responding to the received compliments. Most of the complimentees chose not to accept, amend, or reject the compliment. Instead, they dealt with the compliment implicitly within the interaction, preferring not to directly address the prepositional content of the compliment. It was revealed that the use of strategies depends on the relationship between the complimenter and the complimentee. Their relationship may influence the kind of strategies and words the complimentees use in their responses. The social media users, as they read this study, will be aware of how compliments and compliment responses function and are structures in this online setting, which may incite them to use these two social acts more strategically.